Some Unintended Consequences of Parallel Trade in Pharmaceuticals. (11th August 2014) - Matteucci, Giorgio; Reverberi, Pierfrancesco
Abstract: It is widely argued that international arbitrage, or parallel trade (PT), in patented drugs may increase consumer surplus in the relevant countries but at the expense of R&D investment. We show how the effects of PT depend on the vertical contract (linear pricing or dual pricing) between the manufacturer and the foreign licensee or distributor and on whether and how drug prices are regulated and reimbursed. We find that, contrary to what policy makers generally predict, we should be more concerned with the impact of PT on aggregate consumer surplus than on R&D investment. Copyright © 2014 John Wiley & Sons, Ltd.